Characterization of the growth/survival of Francisella tularensis in selected food matrices - Milke, Donka Todorova (Kansas State University, 2014)
Francisella tularensis is a Gram-negative bacterium that can cause tularemia in humans. The disease can be acquired through several routes, one of which is the ingestion of contaminated food and water. The pathogen has the potential to be used as a biological weapon, and its intentional introduction in the food supply is a possible way to cause public harm. The purpose of this study was to evaluate the growth and/or survival of F. tularensis in food matrices under various storage conditions. Cystine Heart Agar enriched with 2% hemoglobin and supplemented with antibiotics was used to aid the enumeration of the target organism by suppressing the levels of indigenous microflora in foods. During the first portion of the study, the growth/survival of highly virulent F. tularensis subsp. tularensis SCHU S4 strain was investigated in prepared bagged iceberg lettuce stored at two temperatures. F. tularensis counts were significantly different (p≤0.05) among temperature levels for days 1-3, but not day 4. After the first 24 h of incubation, the mean estimates of F. tularensis counts were 1.00 log cfu g⁻¹ lower in lettuce stored at 23±1°C compared to lettuce stored at 6±1°C. Lower recovery rates at higher temperatures are likely due to the more rapid proliferation of naturally present bacteria which can inhibit the growth of F. tularensis. After 48 and 72 h, differences in F. tularensis counts between temperatures were 0.55 log cfu g⁻¹ and 0.3 log cfu g⁻¹, respectively. For the second portion of the experiment, the ability of F. tularensis to grow or survive was evaluated in nine food matrices with variable compositional content (red delicious apples, green bell pepper, shredded iceberg lettuce, strawberries, whole liquid eggs, boneless ham steak, beef hot dogs, 80-20 ground beef, and 2% UHT milk) at 4, 21, and 37°C. F. tularensis grew well in pasteurized whole liquid eggs stored at 21 and 37°C. With the exception of ham, liquid whole eggs, and bell pepper, the pathogen was detected infrequently throughout the duration of the study. Very low recovery rates were obtained for shredded lettuce, hot dogs, and ground beef.
Keywords: Francisella; Select agent; Food